2015
DOI: 10.1007/s10840-015-0020-6
|View full text |Cite
|
Sign up to set email alerts
|

Association between left atrial low-voltage area, serum apoptosis, and fibrosis biomarkers and incidence of silent cerebral events after catheter ablation of atrial fibrillation

Abstract: LA remodeling, estimated by LADmax and LA low-voltage area, has significant relationship with the risk of SCE after AF ablation. Moreover, Fas-Ligand may act as an independent predictor for SCE in the context of AF CA.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
9
0
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 28 publications
1
9
0
2
Order By: Relevance
“…All patients underwent RFA with effective anticoagulation. Previous studies have established the association of CHADS 2 /CHA 2 DS 2 VASc scores with the occurrence of cerebrovascular accident during IPV, 7 , 17 but several studies showed no relationship between these scores and procedure-related thromboembolism. 4 , 18 20 …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…All patients underwent RFA with effective anticoagulation. Previous studies have established the association of CHADS 2 /CHA 2 DS 2 VASc scores with the occurrence of cerebrovascular accident during IPV, 7 , 17 but several studies showed no relationship between these scores and procedure-related thromboembolism. 4 , 18 20 …”
Section: Discussionmentioning
confidence: 99%
“… 3 Additionally, periprocedural diffusion-weighted cerebral magnetic resonance imaging (DW-MRI) has shown that the IPV procedure can lead to subclinical cerebral embolism in up to 48% of patients. 4 8 Previous studies have been performed to evaluate silent cerebral lesions during IPV using DW-MRI as a reference diagnostic method. However, another study suggested that DW-MRI lacks sensitivity, and the authors investigated whether detection of cerebral damage during IPV can be improved by assessing a sensitive biomarker of neuronal injury: protein S100B.…”
Section: Introductionmentioning
confidence: 99%
“…Ancak bu prosedürün en önemli komplikasyonlarından biri, hastaların %1'inde görüle-bilen serebrovasküler olaylardır (3). Hatta difüzyon manyetik rezonans görüntüleme (MRG) ile değerlendirild-iğinde; subklinik serebral emboli sıklığının %48'e kadar yükseldiğini gösteren çalışmalar mevcuttur (4)(5)(6)(7). Bu çalışmalarda AF ablasyonu ilişkili serebral komplikasyonlar difüzyon MRG ile değerlendirilmiştir.…”
unclassified
“…We agree that stroke in atrial fibrillation (AF) appears to be a complex and poorly understood phenomenon. A number of recent studies have demonstrated an association between left atrial electrical remodeling and thrombogenesis [3][4][5][6] suggesting that the underlying left atrial substrate may be an important determinant of stroke risk and that adverse atrial remodeling could convey an increased risk even in the absence of AF itself.…”
mentioning
confidence: 99%